Rancang Bangun Sistem Monitoring dan Controlling Suhu dan Kelembapan pada Cooler Box Ikan Berbasis IOT dengan Metode Logika Fuzzy - Muhammad, Fadhil; Maulana, Eka; Muslim, Muhammad Aziz (Jurnal Mahasiswa TEUB, 2024)
Fish is Indonesia's mainstay product with national consumption reaching 56.48 kg per capita in 2022. However, fish rot quickly after death, especially at high temperatures such as 37°C which accelerates enzyme activity. To maintain freshness, a stable cold chain is needed during distribution and storage. The traditional method of using ice blocks in a cooler box often causes the ice to melt quickly, affecting temperature and humidity, and reducing fish quality. Ice blocks can also injure and cause bruising on the surface of the fish, which opens up gaps for spoilage bacteria to grow faster. In addition, conventional cooler boxes often fail to maintain ideal temperatures, accelerating the decline in fish quality, and potentially damaging the environment. Therefore, this study aims to design and build a temperature and humidity monitoring and controlling system in a fish cooler box based on the Internet of Things (IoT) with the fuzzy logic method. This system uses a DHT22 sensor to read temperature and humidity, ESP32 as a microcontroller, and Blynk Cloud for system monitoring. Fuzzy logic is used to provide a number of benefits to improve the efficiency of temperature and humidity control. The results of the study indicate that the system can work according to the design with the accuracy of DHT22 sensor reading at a temperature of 99.79% and humidity of 98.42%. The fuzzy logic system for thermoelectric cooling system and mist maker shows an accuracy of 98.1% and 98.3%. Keywords: Cooler box, temperature and humidity, thermoelectric cooling system, mist maker, Blynk, Fuzzy Logic